(untitled) (Proceedings of the International Conference on Public Health, 2017)
Education represents an important aspect of public awareness. It is expected that medical education has a great effect in promoting healthy life of medical students. This paper represents a comparison between senior students in faculty of medicine and senior students in non-medical faculty "faculty of business" to find out whether medical education has contributed in improving quality of life of medical students or made no difference. Our questionnaire-based study was conducted on 600 students (300 from each faculty). Dietary habits, healthy habits, Sports and exercise, free time and bad habits were included according to Health Behavior in School-aged Children (HBSC) study protocol questionnaire. Although medical students showed higher level of knowledge about healthy lifestyle, we reported an insignificant difference between lifestyle of medical and non-medical students. Establishment of a behavior towards health-related issues requires more than presence of knowledge. Therefore a complete health programs are needed to raise awareness and encourage behavior development among university students in Egypt.